2010
DOI: 10.1186/1758-5996-2-47
|View full text |Cite
|
Sign up to set email alerts
|

Is exercise a therapeutic tool for improvement of cardiovascular risk factors in adolescents with type 1 diabetes mellitus? A randomised controlled trial

Abstract: BackgroundType 1 diabetes mellitus (T1DM) is associated with a high risk for early atherosclerotic complications especially risk of coronary heart disease.ObjectiveTo evaluate the impact of six months exercise prgram on glycemic control, plasma lipids values, blood pressure, severity and frequency of hypoglycemia, anthropometric measurements and insulin dose in a sample of adolescents with T1DM.Research design and methodsA total of 196 type 1 diabetic patients participated in the study. They were classified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
142
0
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(168 citation statements)
references
References 38 publications
6
142
0
20
Order By: Relevance
“…Studies of training program on group of adolescents with T1DM revealed that regular physical exercise significantly decrease HbA1c [8,18]. Other studies revealed similar significant results [4][5][6]9,19,20] which showed that improvement was associated with the frequency of physical activity [4,20]. Slight decrease in HbA1c was observed with combination of aerobic and muscle strength exercise training program [10,14] and was better with competitive sport [21].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Studies of training program on group of adolescents with T1DM revealed that regular physical exercise significantly decrease HbA1c [8,18]. Other studies revealed similar significant results [4][5][6]9,19,20] which showed that improvement was associated with the frequency of physical activity [4,20]. Slight decrease in HbA1c was observed with combination of aerobic and muscle strength exercise training program [10,14] and was better with competitive sport [21].…”
Section: Discussionsupporting
confidence: 55%
“…Many studies of type 1 diabetes children or adolescent have demonstrated that exercise have a beneficial effect in type 1 diabetes. It lowers blood pressure [4], improves lipid profile [5,6], endurance capacity [7], body composition of fat to muscle mass ratio [8][9][10][11], physical fitness [7], insulin sensitivity [12], bone mineral density [11], vascular function [7], antioxidant capacity [13] and overall quality of the life [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…A 6-month trial of dietary counseling in Italian children and adolescents produced a significant improvement in TC/HDL-C, LDL-C, and non-HDL-C. 218 Another lifestyle intervention trial of 196 adolescents with T1DM demonstrated improvement in lipid levels along with decreases in waist circumference, BMI, and insulin requirement with 6 months of exercise. 230 In that trial, no correlation was seen between duration of DM and lipid levels; however, elevated triglycerides, TC, and LDL-C were seen in 50%, 45%, and 15% of patients, respectively. Few studies have specifically examined the effect of intensive pharmacological therapy on CVD risk factor reduction in children with T1DM, although 1 study suggested a trend toward improved endothelial function after 12 weeks of atorvastatin 20 mg/d.…”
Section: Cvd Risk Factors In Children With T1dmmentioning
confidence: 99%
“…In diabetic animal models, mixed results have been obtained concerning potential positive effects of exercise on islets [17,18]. However, positive effects of exercise on diabetics have been measured on the vasculature [19] and heart disease [20]. The evidence on the effects of exercise on kidney function in diabetics is also mixed and should be approached cautiously in people with already existing kidney disease [21].…”
mentioning
confidence: 99%